Teaching the 21st Century Skills (4Cs) in English Literacy Activities in SMKN 1 Singaraja in Academic Year 2019/2020 - Ratama, I Putu; Padmadewi, Ni Nyoman; Artini, Luh Putu (LPPM Undiksha, 2021)
Literacy program has been echoed by the Minister of education and culture since 2015. Teaching other skills in the implementation of literacy activities are crucial to prepare the students to compete in working field, especially in Vocational School. This study aimed to investigate (1) the kinds of English literacy activities implemented in SMKN 1 Singaraja, (2) how to teach the 21st century skills (4Cs) in English literacy activities in SMKN 1 Singaraja which consisted of preparation, steps and assessment of the 4Cs skills, (3) Teachersâ€™ challenges while teaching the 21st century skills (4Cs) in English literacy activities in SMKN 1 Singaraja. The design of this research was descriptive qualitative. The setting of this research was SMKN 1 Singaraja and the subjects of this research were 120 students and 3 teachers in this school. The techniques of data collection were observation, interview, note taking, document analysis and documentation. The finding showed that (1) there were five English literacy activities implemented in this school namely, reading response journal, news reading program, guiding object commentary, travel itinerary writing and cooperative literacy program. (2) In the implementation of those English literacy activities, the teachers taught the 21st century skills (4Cs). In reading response journal, the 21st century skills taught were critical thinking, collaboration and communication skills. In news reading program and cooperative literacy program, all of those 21st century skills (4Cs) were taught.Â In, guiding object commentary, there were three 21st century skills were taught namely critical thinking, creativity and communication skills. At last, there were three skills were taught in travel itinerary writing namely critical thinking, collaboration and creativity skills (3) In teaching the 21st century skills, the teachers still had challenges in teaching critical thinking, collaboration and communication skills. There was no challenge in teaching creativity skill in English literacy activities. This research was expected to be beneficial for the policymaker, schools, and teachers who had big effort in implementing effective literacy program in schools. Those activities and ways of teaching the 21st century skills could be adopted in order to enhance the level of literacy program.